Imagining the Homeland : Myth, Movement, and Migration in Three Novels by Women from the African Diaspora - Nosalek, Kevin (East Carolina University, 2015)
For immigrant authors of African descent, the impact of postnationalism and the continued subjugation of their native cultures through neocolonialism focuses the writers' pens on subjects of dispersal, either forced or voluntary. In their description of this diasporic movement, these authors write of a desire to re-create an image of the homeland in a hostile hostland. They describe a need to maintain a cultural identity based on a memory of "home" while adapting to a foreign social structure. These opposing desires impede the assimilation process. As opposed to men, women, who fill the traditional role of home-building in their homeland, face greater barriers to the creation of a place of both physical and mental belonging outside of their native cultures. Using Edwidge Danticat's Breath, Eyes, Memory, Chimamanda Adichie's Americanah, and NoViolet Bulawayo's We Need New Names, this thesis examines how contemporary literature written by women from African diasporic communities resists assimilation and acculturation and tells, instead, of the desires for a home and a culture that have been left behind through the process of movement.
Keywords: Literature; African literature; Modern literature; Diaspora; Home; Immigration; Breath, eyes, memory; Americanah; We need new names; Women authors, Black; Group identity in literature; Assimilation (Sociology) in literature; Danticat, Edwidge, 1969- --Criticism and interpretation; Danticat, Edwidge, 1969- . Breath, eyes, memory; Adichie, Chimamanda Ngozi, 1977- --Criticism and interpretation; Adichie, Chimamanda Ngozi, 1977- . Americanah; Bulawayo, NoViolet--Criticism and interpretation; Bulawayo, NoViolet. We need new names